2019
DOI: 10.3892/ol.2019.10991
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated elimination of human cancer cells by a CD40 agonist antibody combined with a PD‑1 antagonist in CD4‑depleted mice

Abstract: The elimination of residual microscopic cancer cells is important cancer treatment. The immunoediting theory describes the balance between the immune system and cancer cells. The current study investigated changes in the immune system during the elimination of cancer cells and evaluated the influence of cluster of differentiation (CD)4 or CD8 depletion. A human squamous cell cancer cell line (SNU1041) was injected in the lateral tongue of immunocompetent mice and the changes in the CD4, CD8, CD11b, CD19, CD40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 45 In addition, it was reported that TNFRSF5 (CD40) agonists could reverse resistance to anti-PD-1 therapy. 46 , 47 Therefore, TNF-related axes seem to play a role in immunotherapy. To our surprise, in our study, we found that TNF-TNFRSF1A and TNF-FAS interactions between CD8 T cells/macrophages/tumor cells and other cells were consistently weaker in nonresponders than in responders, while the TNFSF10/MIF-TNFRSF10D interactions between other cells and endothelial cells and the TNFSF13-related ligand-receptor interactions between pDCs/macrophages and other cells were consistently weaker in responders than in nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“… 45 In addition, it was reported that TNFRSF5 (CD40) agonists could reverse resistance to anti-PD-1 therapy. 46 , 47 Therefore, TNF-related axes seem to play a role in immunotherapy. To our surprise, in our study, we found that TNF-TNFRSF1A and TNF-FAS interactions between CD8 T cells/macrophages/tumor cells and other cells were consistently weaker in nonresponders than in responders, while the TNFSF10/MIF-TNFRSF10D interactions between other cells and endothelial cells and the TNFSF13-related ligand-receptor interactions between pDCs/macrophages and other cells were consistently weaker in responders than in nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, cancer recurrence is not only dependent on the tumorigenic potential of cancer cells but also on the relationship between cancer cells and the immunity of patients. A previous study by our laboratory has shown that decreased expression of CD40L in regional cancer-free lymph nodes is a significant poor prognostic factor (2) and that depletion of CD4 in immunocompetent mice delays the clearance of injected human cancer cells in the tongue (3). These data suggest that the CD40-CD40L interaction can be an important target to improve treatment outcome.…”
mentioning
confidence: 63%
“…Another proposed mechanism of turning 'cold' tumors 'hot' is via CD40 activation using agonist CD40 antibodies [337,375,376]. Long-term clinical responses have been reported in a Phase I trial of tremelimumab + CP-870893 (CD40 agonist) in ICI-naive melanoma [337].…”
Section: Icis Plus Tgf-β Inhibitorsmentioning
confidence: 99%